2014
DOI: 10.1111/aogs.12330
|View full text |Cite
|
Sign up to set email alerts
|

A structured four‐step curriculum in basic laparoscopy: development and validation

Abstract: A four-step curriculum in basic laparoscopy is applicable in residency training. Protected training time correlated with increasing completion rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 32 publications
1
42
0
Order By: Relevance
“…3,6,7,[13][14][15] North American obstetrics and gynecology programs lack a standardized laparoscopy curriculum for residents, despite multiple publications describing its necessity. 7,9,19,21,22 The curricula in most programs may lack aspects of comprehensive curriculum design because they were developed at a local level. 3,13,15 Comprehensive national curricula designed for junior gynecology residents were described in Denmark and the United Kingdom, 9,18 yet neither included a nontechnical skills component.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…3,6,7,[13][14][15] North American obstetrics and gynecology programs lack a standardized laparoscopy curriculum for residents, despite multiple publications describing its necessity. 7,9,19,21,22 The curricula in most programs may lack aspects of comprehensive curriculum design because they were developed at a local level. 3,13,15 Comprehensive national curricula designed for junior gynecology residents were described in Denmark and the United Kingdom, 9,18 yet neither included a nontechnical skills component.…”
Section: Discussionmentioning
confidence: 99%
“…7,9,19,21,22 The curricula in most programs may lack aspects of comprehensive curriculum design because they were developed at a local level. 3,13,15 Comprehensive national curricula designed for junior gynecology residents were described in Denmark and the United Kingdom, 9,18 yet neither included a nontechnical skills component. Previous work has demonstrated that basic task training using VR simulators translates into improved performance in the operating room.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The simulation-based course in flexible bronchoscopy followed an evidence-based mastery learning with a distributed practice approach from a structured four-step model [14]. …”
Section: Methodsmentioning
confidence: 99%